ENGENDERED DANGER AND ENDANGERED GENDER: THE CHURCH AND HOMOSEXUAL CLERGY – A CASE STUDY - Pratt, Douglas (Scriptura, 2004)
The issue of homosexuality is vexing the church throughout much of the world and seems to be most heated around the issue of clergy. Negative reactions to the prospect of the church endorsing homosexual clergy appear to suggest that such clergy pose a sort of ‘engendered danger’ to the very being of the church. Equally, these reactions give the impression that gay clerics are themselves something of an ‘endangered gender’. By taking as my starting point the situation in respect to the New Zealand Methodist Church, I propose to comment on the theme of danger / endangerment that is posed by the issue of clerical homosexuality, and to review a theological approach that might allow for the amelioration of danger and allow for the legitimate acceptance of homosexuality within the church.